Factor structure and measurement invariance of the psychosocial risk factors inventory of NOM-035-STPS-2018 - Cano-Gutierrez, Julio César; Pérez-Morán, Juan Carlos; Bernal-Baldenebro, Brando; Arenas-Meneses, Daniela; Vazquez-Lira, Ramsés; Olguín-Tiznado, Jesús Everardo (Frontiers in Psychology, 2023)
The purpose of the study is to analyze the psychometric properties of the Inventory for the Identification and Analysis of Psychosocial Risk Factors (IIA-PRF) of Reference Guide III proposed in NOM-035-STPS-2018. A total of 2,149 workers in Baja California, Mexico's industrial and education-government sectors, were administered an online inventory version. Preliminary analyses were performed, as well as a Confirmatory Factor Analysis (CFA) based on two models proposed by the standard itself: an eight-factor model (8-FM) and a four-factor model (4-FM). Likewise, based on the results and with the recommendations of the specialists, a three-factor model (3-FM) was proposed. In addition, nested model sequencing methods were subsequently applied to validate the invariance between the origin of the activity. The dimensionality of 3-FM was found to have adequate fit values according to a-priori established criteria. It is concluded that the IIA-PRF does not have the reliability and validity parameters necessary to support interpretations, uses and consequences based on the theoretical structure established by NOM-035-STPS-2018 and that, although the 3-FM presents better reliability and validity indices, it is not invariant in terms of the origin of the activity. Finally, it is recommended to review and adjust the design of the IIA-PRF items to extend the measurement of invariance to other groups of relevance for decision-making in improving the work environment.